2013
DOI: 10.1371/journal.pone.0055394
|View full text |Cite
|
Sign up to set email alerts
|

Infertility Treatment and Umbilical Cord Length–Novel Markers of Childhood Epilepsy?

Abstract: BackgroundEpilepsy is one of the most common neurologic disorders of childhood, affecting about 0.4−0.8% of all children up to the age of 20.MethodologyA population-based retrospective cohort study. Aim was to determine incidence and identify perinatal and reproductive risk factors of epilepsy in children born between 1989 and 2008 among women (n = 43,389) delivered in Kuopio University Hospital. Risk factors of childhood epilepsy were determined by using logistic regression analysis.Principal FindingsThe inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The aim for our study was to evaluate the prevalence of various etiologies of epilepsies and epilepsy syndromes and to estimate cognitive function in a population‐based birth registry. In previous work, we have published an evaluation of perinatal and reproductive risk factors for childhood epilepsy in this cohort …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aim for our study was to evaluate the prevalence of various etiologies of epilepsies and epilepsy syndromes and to estimate cognitive function in a population‐based birth registry. In previous work, we have published an evaluation of perinatal and reproductive risk factors for childhood epilepsy in this cohort …”
mentioning
confidence: 99%
“…In previous work, we have published an evaluation of perinatal and reproductive risk factors for childhood epilepsy in this cohort. 26…”
mentioning
confidence: 99%
“…However, the results were not adjusted for important potential confounders including maternal history of epilepsy and maternal education. The association between ART and childhood epilepsy was confirmed in a recent study by Räisänen et al ,. whereas Klemetti et al .…”
Section: Commentsmentioning
confidence: 57%
“…8 However, the results were not adjusted for important potential confounders including maternal history of epilepsy and maternal education. The association between ART and childhood epilepsy was confirmed in a recent study by R€ ais€ anen et al 21 , whereas Klemetti et al only showed a slight tendency towards an association with IVF or ovulation induction. 22,23 The studies did not include information on the infertile parents with no treatment, and none of the previous studies investigated infertility as a continuous measure or assessed the association with various types of epilepsy.…”
Section: Commentsmentioning
confidence: 77%
“…However, these children were only followed until the age of two years 35,36 . Additionally, a cohort study aiming to identify risk factors of childhood epilepsy showed an association with assisted reproductive technology 37 . However, these studies did not account sufficiently for potential confounders, including parental infertility.…”
Section: Discussionmentioning
confidence: 99%